Consumo de publicidade: corpo, vestuário e atitude na construção do imaginário de marcas de moda feminina - Estrada, Ana Cristina Puglia Duque (2010)
In this research, we have, as a problem to be investigated, the impact of fashion communication in its reception. We intend to understand if the reception (people who works with fashion) identify differences between fashion brands and the imaginary given to them by press (magazines) and, as a second question, we will identify the imaginaries of body fashion presented in the magazines analyzed. Although the media press is used, in the most often, as a sustainable media, and it is chosen because it is an information resource of a more traditional fashion to people interested on it. Vogue's magazine choice occurred in some steps: exploratory research with Marketing and Commercial professionals, from national brands, whose results showed that around 70% of female costumes announced on Elle on September 2008, was also in Vogue magazine and 50% announced in Estilo magazine; this is one of the reason why Vogue is considered, all over the world, as a privileged place to launch an advertisement and la lifestyle Campaign There are some assumptions that the repetition of visual and conceptual models by almost all brands, complicates the differentiation of the imaginaries worlds of each one, and just the brands able to have an investment of integrated marketing, using also others options of communication, achieve a construction of brand image. It is a project anchored in a theoretic and conceptual picture divided in two groups of interest: consumption and media, and body and fashion. To develop it, we use a qualitative methodology and we will use bibliographic, documentary and empiric research. The bibliographic research will ground the discussions about consumption, media, body and fashion relations, trying to understand how they are related to the contemporary society. The documentary research, whose corpus is formed by advertisements published in Vogue Brazil, on April and September, from 2000 to 2009, will allow us to identify and analyze the bodies and brands representations, through the methodology of the Discourse Analysis of French School . And, finally, the empirical (of reception), we will use the qualitative technical through an in-depth research half-structured with just one interviewee.